Stable electron-irradiated [1- 13 C]alanine radicals for metabolic imaging with dynamic nuclear polarization - Rooney, Catriona H. E.; Lau, Justin Y. C.; Hansen, Esben S. S.; Christensen, Nichlas Vous; Dang, Duy A.; Petersson, Kristoffer; Tullis, Iain D. C.; Vojnovic, Borivoj; Smart, Sean; Myers, William; Richardson, Zoe; Lewis, Jarrod; et al. (Science advances, 2025)
Dissolution dynamic nuclear polarization (dDNP) increases the sensitivity of magnetic resonance experiments by >10 4 -fold, permitting isotopically labeled molecules to be transiently visible in magnetic resonance imaging scans. dDNP mechanistically takes place at ~1 K and requires unpaired electrons and microwaves. These electrons are usually chemical radicals, requiring removal by filtration prior to injection into humans. Alternative sources, such as ultraviolet irradiation, generate lower polarization and require cryogenic transport. We present ultrahigh–dose rate electron irradiation as an alternative for generating nonpersistent radicals in alanine/glycerol mixtures. These are stable for months at room temperature, quench spontaneously upon dissolution, are present in dose-dependent concentrations, and generate comparable nuclear polarization (17%) to trityl radicals used clinically (19%) through a previously unknown mechanism we believe to involve partial ordering and electron-electron interactions. Owing to the large radiation doses required, this process is sterilizing, permits imaging of alanine metabolism in vivo in the rat kidney, and may aid clinically translating dDNP. Six-MeV electrons generate stable radicals for more accessible metabolic imaging with dDNP through a previously unknown mechanism.